New Trends in Lithium Niobate: From Bulk to Nanocrystals - László Kovács (MDPI AG, 2021)
The recent Special Issue on lithium niobate (LiNbO3) is dedicated to Prof. Schirmer and his topics and contains nineteen papers, out of which seven review various aspects of intrinsic and extrinsic defects in single crystals, thin films, and powdered phases; six present brand-new results of basic research, including two papers on Li(Nb,Ta)O3 mixed crystals; and the remaining six are related to various optical and/or thin film applications.